"#Bughead Is Endgame": Civic Meaning-Making in Riverdale Anti-Fandom and Shipping Practices on Tumblr. (September 2022) - Burkhardt, Emily; Trott, Verity; Monaghan, Whitney
In this paper, we seek to understand how shipping and anti-fan practices intersect to create meaningful audience engagement and civic discourse about contemporary social and political issues in the "politics of viewing" CW's adaptation of Riverdale . By examining tagged posts from January 3, 2017 to June 26, 2019, we elicit how fan-rhetoric operates in a digitally networked environment and interrogate the intra-fan rivalries between shippers, anti-shippers, and anti-fans that underpin the Riverdale fandom on Tumblr. In doing so, we begin to sketch out a taxonomy of shipping-specific anti-fan practices, extending Gray's work into different types and modes of anti-fandom to consider the role shipping plays within consumption practices, fandom stratification, and the production of civic discourse online.